Implementasi Metode Waterfall pada Perancangan Sistem Helpdesk Berbasis Mobile sebagai Media Pengaduan dan Monitoring Layanan One Gate Portal - Afif Efendi; Joko Erwanto; Nurdin Suryana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The development of information technology requires companies to provide responsive, transparent, and integrated services, particularly in managing customer complaints. PT Esa Parkir Indonesia, as a provider of one gate portal services for residential and office areas, still encounters issues in handling device malfunction reports submitted through conventional communication media such as telephone calls and instant messaging applications. These methods are considered ineffective due to the absence of centralized data recording, limited monitoring of work progress, and lack of transparency regarding technicians’ activities in the field. This study aims to design and implement a mobile-based helpdesk system as a complaint and monitoring platform for one gate portal services using the Waterfall method. The system enables clients to submit reports independently, monitor ticket status, and access detailed information about technicians’ work in real time. Additionally, the system incorporates location validation to ensure that technicians are present at the designated service area before closing a ticket, thereby minimizing report manipulation. The system development utilizes CodeIgniter 3 as the backend framework and Flutter for mobile application development. The results indicate that the proposed helpdesk system improves the effectiveness of complaint management, enhances control over technician performance, and increases transparency and client satisfaction with the provided services.